Foreign Divestment Decisions in Banking − Case Nordea in Poland - Lahtinen, Eveliina (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
In the 21st century, the realignment of multinational companies’ business scope has become a major issue globally. A very prominent part of the global realignment process, alongside with mergers, acquisitions and alliances, are foreign divestments. Foreign divestments have become an integral aspect of international business since they are now widely practiced by MNCs from a growing and diverse range of home countries and host economies. The objective of this thesis is to identify the factors that contribute to foreign divestment decisions in the banking sector. This thesis is a qualitative research with a single case study approach. The chosen case of this thesis is the divestment made by the internationally operating Nordic financial service group, Nordea, in Poland in 2013. The empirical findings were obtained by interviewing experts from the case company and the interviews were conducted as theme interviews using the four themes that according to the theoretical framework of this thesis are the contributing factors in foreign divestment decisions: (1) environmental stability, (2) attractiveness of current operations, (3) strategic fit, and (4) governance issues. The empirical findings of this thesis suggest that there were four dominant contributors to the foreign divestment decision of the case company: (1) host government regulations, (2) strategic considerations, (3) economic outlook, and (4) interested buyer. The empirical findings mostly support the accuracy of the selected framework as the first three theme groups were found to be major contributors also in the case company’s foreign divestment. However, the importance of the fourth theme group, ‘governance issues’, is not supported by the findings of this thesis. Furthermore the findings suggest that in addition to the groups presented in the framework, also timing can be an import factor in divestment decisions. Three managerial recommendations can be drawn from the findings of this thesis: (1) If a foreign divestment decision is the best course of action due to strategic reasons, it should not be avoided; (2) The pre-investment due diligence processes should not be ignored since it can help to avoid unwanted divestments; and (3) Companies should concentrate on building good relationships with the host government since it can facilitate business activities in the host country.